2021
DOI: 10.14569/ijacsa.2021.0120180
|View full text |Cite
|
Sign up to set email alerts
|

An Accessibility Evaluation of the Websites of Top-ranked Hospitals in Saudi Arabia

Abstract: Hospital websites offer the potential to improve healthcare service delivery. They can provide up-to-date information and services to patients, at low cost and regardless of their level of abilities. This, in turn, can reduce overcrowding in hospitals and reduce spread of disease, especially in circumstances like the current COVID-19 pandemic. It is, therefore, imperative for designers to ensure the accessibility of hospital websites to the widest possible range of people. This study aims to evaluate the acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…In addition, the websites were generally below average with regard to usability due to excessive page size, the presence of numerous broken links, failure to include a search feature, and providing information in only one language. Most of these accessibility and usability violations are consistent with findings previously reported in the healthcare domain [ 54 – 57 ]. Prior studies found issues with links being empty, color contrast, alternative text for linked images, headings, and keyboard accessibility.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the websites were generally below average with regard to usability due to excessive page size, the presence of numerous broken links, failure to include a search feature, and providing information in only one language. Most of these accessibility and usability violations are consistent with findings previously reported in the healthcare domain [ 54 – 57 ]. Prior studies found issues with links being empty, color contrast, alternative text for linked images, headings, and keyboard accessibility.…”
Section: Discussionsupporting
confidence: 91%